On nearly m-supplemented subgroups of finite groups - Guo, J.; Zhang, J.; Miao, L. (Український математичний журнал, 2014)
A subgroup H is called nearly ℳ-supplemented in a finite group G if there exists a normal subgroup K of G such that HK ⊴ G and TK < HK for every maximal subgroup T of H. We obtain some new results on supersoluble groups and their formation by using nearly ℳ-supplemented subgroups and study the structure of finite groups. Підгрупу H називаємо майже M-доповненою в скінчєнній групі G, якщо існує нормальна підгрупа K групи G така, що HK ⊴ G i TK < HK для кожної максимальної підгрупи T групи H. Отримано деякі нові результати про суперрозв'язні групи та їх утворення за допомогою майже ℳ-доповнених підгруп та досліджено структуру скінченних груп.